Effect of root promoter on tobacco (Nicotiana tabacum L.) growth and nutrient accumulation at Hunan Province, China - Li, Yuanhuan; Azman, Elisa Azura; Ismail, Roslan; Deng, Xiaohua; Dhar, Shiva; Noviardi, Rhazista; Citraresmini, Ania; Zi, Tao; Yang, Lili; Aalruz, Hasan; Ababneh, Hazim S.; Abaraogu, Ukachukwu O.; et al. (Nature Research, 2026)
Early root establishment is vital for tobacco survival under low-temperature stress in southern China. This field study evaluated potassium humate (PH), Hymexazol and Isorothiolane emulsifiable concentrate (HIEC), and chitosan (CS). Compared to the control group (CG), PH and HIEC emerged as the most effective treatments. Agronomic traits (e.g., root length, leaf number) increased by 5.41% to 24.31% and 15.00% to 80.91% relative to the CG, respectively, while dry matter and nutrient accumulation (nitrogen, phosphorus, potassium) significantly enhanced by 10.84% to 64.83% and 28.03% to 100%, respectively. Mechanistically, PH employed a “Soil-Optimization Strategy,” improving soil pH and organic matter while maintaining microbial diversity. Conversely, HIEC utilized a ‘Functional Selection Strategy,’ stimulating growth by selectively enriching protective genera such as Gaiella and Sphingomonas (reaching relative abundances of 11.36% and 3.60%, respectively, compared to the CG), despite reducing overall bacterial diversity. Furthermore, correlation analysis revealed a positive feedback loop where root expansion enhanced Nitrogen/Potassium uptake, boosting relative chlorophyll content (SPAD) and fueling biomass accumulation. These findings highlight that distinct ecological pathways, specifically soil amelioration and functional microbiome selection, effectively drive crop resilience, providing practical cultivation measures for the tobacco industry to overcome adverse climatic conditions.